Psychometric Properties of the South Oaks Gambling Screen Revised for Adolescents in Chinese Adolescent Gamblers - Hui Zhou; Hui Zhou; Juliet Honglei Chen; Juliet Honglei Chen; Haofeng Ling; Kwok Kit Tong; Anise M. S. Wu; Anise M. S. Wu (Frontiers Media S.A., 2022)
Objectives: Adolescent gambling is a public health concern of increasing importance. The lack of comprehensive evaluations on adolescent gambling disorder (GD) assessment tools hinders the timely detection of Chinese adolescents with gambling problems. This study aimed to evaluate the psychometric properties of South Oaks Gambling Screen-Revised for Adolescents (SOGS-RA) and determine its optimal screening cutoff score among Chinese adolescent gamblers to address this gap.Methods: We surveyed 1407 Chinese secondary school students aged 11-19 years in Macao, China, among which 258 past-year gamblers' data was used for assessing SOGS-RA's performance in detecting risk for adolescent GD.Results: SOGS-RA displayed satisfactory reliability and validity for assessing probable GD among Chinese adolescent gamblers. Under the DSM-5 GD framework, we proposed ≥4 as SOGS-RA's optimal cutoff score of screening for probable GD and further identified 5.8% of past-year gamblers prone to probable GD in the present study.Conclusion: SOGS-RA can provide a reliable and valid assessment of adolescent' GD risk in the Chinese context, facilitate early identification of probable GD cases, and alleviate the public health concern for Chinese adolescents.